2013
DOI: 10.1509/jm.11.0610
|View full text |Cite
|
Sign up to set email alerts
|

When Do Transparent Packages Increase (or Decrease) Food Consumption?

Abstract: Transparent packages are pervasive in food consumption environments. Yet prior research has not systematically examined whether and how transparent packaging affects food consumption. The authors propose that transparent packaging has two opposing effects on food consumption: it enhances food salience, which increases consumption (salience effect), and it facilitates consumption monitoring, which decreases consumption (monitoring effect). They argue that the net effect of transparent packaging on food consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 52 publications
4
86
0
2
Order By: Relevance
“…In turn, examples of food abnormality in retail settings are rare; it accordingly offers a very specific cue that consumers might use to infer quality. Furthermore, most fresh food products (e.g., fruit, vegetables) are not subject to extensive packaging; most grocery stores offer them loose or packaged in transparent plastic (Deng & Srinivasan, ). Thus, this product category offers few extrinsic quality cues (Grunert, Bredahl, & Brunsø, ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In turn, examples of food abnormality in retail settings are rare; it accordingly offers a very specific cue that consumers might use to infer quality. Furthermore, most fresh food products (e.g., fruit, vegetables) are not subject to extensive packaging; most grocery stores offer them loose or packaged in transparent plastic (Deng & Srinivasan, ). Thus, this product category offers few extrinsic quality cues (Grunert, Bredahl, & Brunsø, ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In the United States, but not in Denmark, we also observe more use of transparent packaging for regular products, something that might affect perceived food freshness and healthiness (Simmonds & Spence, ; Simmonds et al, ), but also consumption amount (Deng & Srinivasan, ).…”
Section: Resultsmentioning
confidence: 85%
“…Decrease in attractiveness in the case of transparent packaging was also found in the study of Vilnai-Yavetz and Koren (2013) where it was shown that transparent packaging is perceived as less aesthetic. By connecting these findings with the previously mentioned research (Deng & Srinivasan, 2013) that pointed out the importance of the product type while analysing the influence of transparency, the second hypothesis was formulated:…”
Section: Problem Statementmentioning
confidence: 81%